BMIT facility at the Canadian Light Source: Advances in X-ray phase-sensitive imaging. Issue 12 (December 2016) - Wysokinski, T.W.; Ianowski, J.P.; Luan, X.; Belev, G.; Miller, D.; Webb, M.A.; Zhu, N.; Chapman, D.
Highlights: BMIT provides X-ray imaging capabilities used to address problems in medicine. Investigating the response of CF upper airways to inhalation of bacteria. Inhalation of bacteria triggers ASL secretion that removes the pathogen. Phase-sensitive imaging allows for conducting live animal experiments for in vivo TERM studies. Abstract: The BioMedical Imaging and Therapy (BMIT) facility [1, 2] located at the Canadian Light Source, provides synchrotron-specific imaging and radiation therapy capabilities. There are two separate beamlines used for experiments: the bending magnet (05B1-1) and the insertion device (05ID-2) beamline. The bending magnet beamline provides access to monochromatic beam spanning a spectral range of 15–40 keV, and the beam is 240 mm wide in the POE-2 experimental hutch. Users can also perform experiments with polychromatic (pink) beam. The insertion device beamline was officially opened for general user program in 2015. The source for the ID beamline is a multi-pole, superconducting 4.3 T wiggler. The high field gives a critical energy over 20 keV. The optics hutches prepare a beam that is 220 mm wide in the last experimental hutch SOE-1. The monochromatic spectral range spans 25–150+ keV. Several different X-ray detectors are available for both beamlines, with resolutions ranging from 2 μm to 200 μm. BMIT provides a number of imaging techniques including standard absorption X-ray imaging, K-edge subtraction imaging (KES), in-line phase contrast imaging (also known as propagation based imaging, PBI) and Diffraction Enhanced Imaging/Analyzer Based Imaging (DEI/ABI), all in either projection or CT mode. PBI and DEI/ABI are particularly important tools for BMIT users since these techniques enable visualization of soft tissue and allow for low dose imaging.